Structure, bioactivities and applications of the polysaccharides from Tricholoma Matsutake: a review - LI,Mengjiao (2022)
Abstract Tricholoma Matsutake is an important edible mushroom that has been artificially cultivated and used as a food and medicinal ingredient in traditional Chinese medicine. In the past decades, many researchers have reported that Tricholoma Matsutake Polysaccharides (TMP) possess various bioactivities, including anti-tumor, immunomodulatory, anti-oxidation and anti-aging. The structural characteristics of TMP were studied by GC-MS, LC-MS, NMR, and FT-IR, and the structure-activity relationship of TMP biomolecular was analyzed. This paper reviews the progress of TMP extraction, purification, structure characterization and application.